Efektivitas terapi shalat bahagia untuk meningkatkan self acceptance pada siswa sekolah menengah atas - Yugo Al Ghaffar; Sigit Muryono (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The purpose of this research is to increase self-acceptance through group guidance using happy prayer therapy. This research is a one-group pretest-posttest experimental research with purposive sampling. The sample consisted of 12 grade 11 students at SMAN 60 Jakarta. Research data were analyzed using the Mann-Whitney test with the help of SPSS Ver.26 software. Can be known from the results of the Sig calculation. 0.000 < 0.05 so H₀ is rejected and Hₐ is accepted and proven correct. The results of the calculations that have been carried out show that the Sig. < 0.05, which means the result is significant. This shows that the application of happy prayer therapy can increase the self-acceptance of 11th-grade students of SMAN 60 Jakarta